Standardization of green gram based meat analogues - Nisha (Department of Home Science, College of Horticulture, 2008)
Meat analogue, a simulated product that resembles meat, is suggested as the food for future owing to its nutritional qualities, beneficial health effects and sensory characteristics. In the present study an attempt was made to develop a product possessing both the nutritional and sensory characteristic of meat. It is health beneficial and at the same time is at par with the shortcomings of meat. Meat analogues were prepared using green gram as the base, blended with soya bean and wheat in different proportions. Gluten was used as a texturizing agent and spices like ginger, garlic, pepper and cinnamon were used for flavouring. Totally ten treatments were tried with different proportions including one control with 100 per cent green gram. A standard meat recipe was prepared by replacing meat with the developed products and were evaluated organoleptically using a nine point hedonic rating scale. Three treatments were selected based on maximum index scores, T4 (107.75), control (93.73) and T6 (88.93). The selected three products were packed in metallised polyester polyethylene laminate pouches and kept for shelf life studies for a period of six months. Chemical constituents, sensory qualities and microbial load were analyzed during the initial period, third and sixth month of storage. The products were also subjected to benefit cost analysis by comparing with a similar product available in the market and also with fresh meat and mutton. Meat analogue was observed to be a good source of protein; with a maximum protein content in T6 (26.00g per 100g), invisible fat; which ranged from 1.23g to 2.67g 100g-1 with a maximum fat content in T4, fibre; ranging from 1.33g to 1.82g 100g-1 with T6 having the maximum fibre content, and minerals like calcium (276mg 100g-1), potassium; ranging from 72.00mg to 73.00mg 100g-1, phosphorus; ranging from 177.94mg to 190.85mg 100 g-1 and iron ranging from 1.77mg to 1.89mg 100 g-1. However, on storage there was a significant reduction in the nutrients. A gradual increase in the microbial load was also noticed with the advancement of storage period. The bacterial and the fungal load increased significantly, from 0.167 to a maximum of 2.5 x 106 cfu g-1 and from zero to 1.667 x 103 cfu g-1 respectively, whereas the yeast count remained insignificant with a maximum count of 0.833 x 103 cfu g-1, even at the end of the storage period. However no insect infestation was noticed till the end of storage. Organoleptic evaluation was done by preparing a recipe as in the case of treatment selection. The evaluation revealed that there was decrease in the organoleptic attributes which affected the over all acceptability of the products. High over all acceptability was observed for T4 (5.97). This was mainly contributed by the high scores for attributes like colour, appearance, taste and texture in the third month and high score for flavour, texture and taste during the sixth month. The price of the developed products is comparatively higher than its available substitute in the market. The cost can be reduced considerably through large scale production. Hence, considering the health benefits compared to red meat, cost factor alone cannot be considered as a constraint in the development of the meat analogues. Therefore in this study, treatments T4 (60% green gram, 10% soya and 30% wheat) and T6 (80% green gram, 10% soya and 10% wheat) with comparable nutritional qualities and acceptability can be recommended as a meat analogue for popularization and large scale production.